KAJIAN SIFAT MAGNETIK DARI PASIR BESI PANTAI LOGENDING KABUPATEN KEBUMEN - Bilalodin Bilalodin (Molekul, 2010)
Study on magnetic properties of iron sand on the Logending beach sand has been done. The research aims to identify the mineral content and characterization of magnetic properties on the Logending beach sand. The irond sand samples taken from the Logending beach with several lokation. Sand then dried, determined density and magnetic content is separated using a permanen magnet. The iron sand were analyzed using XRD ( X-ray difraction) and characterization of magnetic properties using the VSM (Vibrating sample magnetometer). The research shows that minerals are contained hematit (Fe2O3), with a value of susceptibility is 0.43 x10-6 m3/kg. The main magnetic mineral of iron sand from logending beach is paramagnetic.